2019
DOI: 10.1111/1753-6405.12858
|View full text |Cite
|
Sign up to set email alerts
|

What young Australians think about a tax on sugar‐sweetened beverages

Abstract: Objective: To determine support for a tax on sugar‐sweetened beverages (SSBs) among young Australian adults and the potential impact on SSB consumption if a tax is introduced. Methods: Cross‐sectional convenience survey of Australians aged 18–30 years sampled in the City of Greater Geelong, Australia, in November–December 2017. Results: A total of 1,793 responses were recorded. Overall, 48% supported a tax on SSBs, which increased to 74% and 72% if tax revenue was allocated to subsidising fruit and vegetables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 18 publications
1
24
1
Order By: Relevance
“…Furthermore, in the UK the measure is targeted at drink manufacturers and the tax revenues will be devoted to health promotion activities, aspects that are linked to a higher level of support. 24,29,30,32,33 Our data support this thesis because, when participants were consulted about other types of price measures, such as tax relief and subsidies on healthy foods, before being asked about the tax, support rose to 70%, equalling that of the UK. This leap was particularly marked among people professing ideological alignment with the political centre and right, and among teenagers and young adults (ages 18-29 years), as was the case in Australia.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Furthermore, in the UK the measure is targeted at drink manufacturers and the tax revenues will be devoted to health promotion activities, aspects that are linked to a higher level of support. 24,29,30,32,33 Our data support this thesis because, when participants were consulted about other types of price measures, such as tax relief and subsidies on healthy foods, before being asked about the tax, support rose to 70%, equalling that of the UK. This leap was particularly marked among people professing ideological alignment with the political centre and right, and among teenagers and young adults (ages 18-29 years), as was the case in Australia.…”
Section: Discussionmentioning
confidence: 53%
“…The proposed tax received majority support (66.9% of the sample), and higher than that observed in countries such as France (57.7%), 29 the USA (40%), 26 Germany 25 and Australia (48%). 30 Only one recent survey in the United Kingdom (UK) showed itself more favourable to this type of tax, with 70% in support, 31 though at the time the UK survey was carried out, the tax had already been announced by the Government, and support for such measures is known to increase after their implementation. 13 In Catalonia, the only Autonomous Region in which the tax has been introduced, 12 the level of support also reached 70%, though the difference with respect to the rest of Spain was not statistically significant (data not shown in the tables).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis performed by Miller et al on the data coming from two surveys: a face-to-face survey conducted in 2014 and CATI survey in 2017, also showed that persons who attained higher levels of education expressed greater support for SSB tax than those with lower levels of education [59]. The acceptance of a sugar tax was frequently much greater if the tax revenue was to be allocated to obesity prevention, subsidies on healthy food or programmes promoting physical activity [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, surveys of policy influencers revealed 57% support for taxes on foods and beverages, while support for public nutrition education received almost universal support (99%) [54]. In two other Australian studies, support for taxation increased when intentions to dedicate revenue to health initiatives were made clear [55, 56]. Dedicating at least 50% of revenue generated to programs that support health has been recommended [16].…”
Section: Challengesmentioning
confidence: 99%